2020
DOI: 10.3390/ijerph17145200
|View full text |Cite
|
Sign up to set email alerts
|

How Do Combustion and Non-Combustion Products Used Outdoors Affect Outdoor and Indoor Particulate Matter Levels? A Field Evaluation Near the Entrance of an Italian University Library

Abstract: Particulate Matter (PM) is a well-known health risk factor and pollutes both outdoor and indoor air. Using PM as an air pollution indicator, the aims were to assess outdoor and indoor air pollution due to combustion and/or non-combustion products used outdoors and to compare the PM levels emitted by different products. PM with an aerodynamic diameter ≤10, 4, 2.5 and 1 µm (PM10, PM4, PM2.5, PM1) was simultaneously measured in two areas, respectively, indoors (with smoking ban) and outdoors (where people commonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…Most of these studies have reported on IAQ levels before, during and after heated tobacco product use within an experimental indoor environment, with a single study reporting on IAQ levels during and after experimentally controlled heated tobacco product use within a non-operational nightclub which featured an external smoking area (Kaunelienė et al, 2019). Two additional studies reported on heated tobacco product use within different models of passenger car (Schober et al, 2019;Savdie et al, 2020) whilst a single study detailed the effects of heated tobacco product use on outdoor air quality (Cammalleri et al, 2020).…”
Section: Chemical Characterisation Studiesmentioning
confidence: 99%
“…Most of these studies have reported on IAQ levels before, during and after heated tobacco product use within an experimental indoor environment, with a single study reporting on IAQ levels during and after experimentally controlled heated tobacco product use within a non-operational nightclub which featured an external smoking area (Kaunelienė et al, 2019). Two additional studies reported on heated tobacco product use within different models of passenger car (Schober et al, 2019;Savdie et al, 2020) whilst a single study detailed the effects of heated tobacco product use on outdoor air quality (Cammalleri et al, 2020).…”
Section: Chemical Characterisation Studiesmentioning
confidence: 99%
“…In fact, the presence and continuation of these information sources are threatened by a variety of disaster variables, including both natural and human-caused disasters. The university library is one of the main places for lecturers and students to study, making it a public place synonymous with great danger (Cammalleri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in recent years, how to evacuate safely, effectively, and quickly has become a very hot research topic. As one of the important places for teachers and students to study, the university library is a typical public place with major hazards [ 2 ]. The scale of university libraries tends to expand continuously, the functions tend to be diversified, the collection of books is large, the fire load is large, and personnel are dense.…”
Section: Introductionmentioning
confidence: 99%